Rationalization of Legally Determined Expenditure as a Condition for Strengthening Financial Accountability - Ruśkowski, Eugeniusz; Zawadzka-Pąk, Urszula (Public Governance, Administration and Finances Law Review, 2018)
The main purpose of this article is to analyse the relationship between financial accountability and legally determined expenditure. According to the adopted research hypothesis, increasing the financial accountability requires taking specific actions in the field of the legally determined expenditure. As the article is theoretical, it does not present the results of the empirical research; the formal-dogmatic method was used to interpret the content of legal acts and jurisprudence of the Constitutional Tribunal, as well as the non-obstructive method to analyse the foreign and Polish literature presenting the results of both theoretical and empirical research. In the article, having presented in the introduction the methodological issues, first, the principle of common good, the financial accountability, and the legally determined expenditure will be first explained. Next, the solutions for the rationalization of the legally determined expenditure will be proposed. We conclude that their implementation should increase the financial accountability to strengthen the constitutional principle of the common good.